A Technology-Based, Financially Sustainable, Quality Improvement Intervention in a Medical Journal for Bilingualism from Submission to Publication - Bachelet-Norelli, V (John Wiley and Sons Inc, 2023)
While English is the dominant language in scientific literature, there are many reasons for introducing bilingualism in academic journals. Bilingualism has generally been avoided due to the perception of high costs and possible inconsistencies between the source language article and the translated version. A medical journal based in Santiago, Chile, carried out a two-year-long quality improvement intervention to overhaul the peer review, copyediting, translating and publication technologies to ensure full bilingualism from submission to online publication. The outcomes are full bilingualism for articles submitted in Spanish and simultaneous publication of both language versions while not compromising the financial sustainability of the journal. © 2023 The Authors. Learned Publishing © 2023 ALPSP.